PUZZLING ENGINE: A DIGITAL PLATFORM TO AID THE REASSEMBLING OF FRACTURED FRAGMENTS - R. D. L. Hernandez; S. Vincke; M. Bassier; L. Mattheuwsen; J. Derdeale; M. Vergauwen (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2019)
The reassembling of fractured fragments is a paramount task in the fields of digital heritage documentation and reconstruction of archaeological artifacts and monuments. This process is typically carried out by manually puzzling matching clues such as decoration,shape, contour, etc. This labor poses a challenge for restorers as fractured fragments are fragile, deteriorated and in some cases bulky. In order to aid experts in this meticulous and time-consuming process, a puzzling engine is developed with the aim of providing the user with tools to facilitate the reassembling of 3D digital fractured fragments. The assisting tools that compose the puzzling engine include 3D manipulation, reference plane alignment, segmentation, and registration. Furthermore, a Virtual Reality (VR) environment is presented as an alternative matching tool. This allows the user to have an intuitive understanding of the fragments in terms of scale, texture, materials, etc., thus facilitating and speeding up the reassembling process. To show the potential of the proposed tool, the engine is tested by archaeologists not only to puzzle classical stone fragments but also to match deteriorated ancient Egyptian rock tomb blocks.